Spanish and other languages in abstracts’ versions in Totonac - Ruiz Velasco, Liliana (2023)
The article deals with a subject scarcely treated, which is the translation in Totonac. For this purpose, a corpus of 38 abstracts written in Totonac was collected among the terminal works for a universitary degree. Specifically it was analyzed the presence of other languages and vocabulary coming from Latin, Spanish and English was found. Latin vocabulary appears by being texts of a scientific discourse tradition, while the other two languages appeared as loanwords. Only a few words have gone through an integration process on the target language. Moreover, it is proposed that we are dealing with cases of transference of a word from one language to another. These loanwords comprised lexical items (among the domains of science, maths, school, everyday life, technology, religion and farming) as well as grammatical ones. Finally, there is a third type of insertion, on which the Spanish word is used in order to give a more precise reading in the indigenous language.